A multicenter analysis of inpatient antibiotic use during the 2015–2019 influenza seasons in the United States: Untapped opportunities for antimicrobial stewardship. Issue 1 (11th August 2022) - Yu, Kalvin C.; Gupta, Vikas; Kabler, Heidi; Watts, Janet A.; Amiche, Amine
Abstract: Outpatient antibiotic use increases during winter months, but information on temporal changes in inpatient antibiotic use in US hospitals is limited. The use of certain inpatient antibiotics, including extended-spectrum cephalosporins, macrolides, and tetracyclines, was strongly associated with influenza activity during the 2015–2019 viral respiratory seasons.